A comparison of the apical extrusion of debris by tapering in rotary systems: in vitro experimental study - Eshaghali Saberi; Shima Bijari; Farshid Gholami; Ebrahim Mohtashami; Forough Farahi (Exploration of Medicine)
Aim: Apical extrusion of debris during root canal preparation can lead to inflammation, flare-ups, and delayed recovery. Therefore, instrumentation techniques that minimize debris extrusion are crucial. This study aimed to compare the apical extrusion of debris by four single-file, full-sequence rotary systems with different tapers. Methods: In this in vitro study, 68 human maxillary lateral incisor teeth with identical root lengths and canal curvatures of less than 10 degrees were used. The teeth were randomly assigned to four experimental groups (n = 17) based on the instrument type: One-Shaped (25, 0.06), 2-Shaped (25, 0.04), Hyflex (25, 0.08), and Neoniti A1 (25, 0.08). Canal preparation was performed according to the manufacturer’s instructions for each file. Extruded debris was collected in pre-weighed vials, and after drying in an incubator, the amount of debris was determined by measuring the weight difference of the vials before and after preparation. Data were analyzed using SPSS 20, with a one-way analysis of covariance (ANOVA) and Tukey’s post hoc test at a significance level of 0.05. Results: The amount of extruded debris in the One-Shaped file was significantly higher than the extruded debris amount in Neoniti A1 (p = 0.049), Hyfex (p = 0.013), and the 2-Shaped file (p = 0.003). Conclusions: The null hypothesis was not invalidated due to significant differences in debris extrusion between the instruments observed in the present investigation. Within the limitations of the present study, the One-Shaped file was associated with higher debris extrusion due to the taper design and other system-specific characteristics. Clinical studies are required to assess whether these findings have an impact on the clinical outcome.